IMPLEMENTATION OF THE RADEC LEARNING MODEL TO IMPROVE HIGH LEVEL THINKING SKILLS IN IPAS COURSES - Indani Damayanti; Muhammad Iqbal Al Ghozali; Islahuddin Islahuddin (Universitas Majalengka, 2023)
This research is motivated by the need for a learning model that is able to facilitate students in developing higher-order thinking skills. So the purpose of this study was to describe the RADEC learning model as an alternative learning model that is considered to be able to improve the development of higher order thinking skills of elementary school students in science subjects. This research method used the Single Subject Research method involving 4 fifth grade elementary school students as research subjects. One solution to help develop higher-order thinking skills in this study is to use the RADEC (Read-Answer-Discuss-Explain and Create) learning model. This is evidenced by the very low proportion of overlap in the subject, which is 0% which indicates that the RADEC learning model has a positive effect on students' higher order thinking skills. This increase is assisted by learning syntax which can develop higher order thinking skills. Conclusion So this research is a RADEC learning model capable of helping to improve students' higher order thinking skills. Penelitian ini dilatarbelakangi oleh kebutuhan akan model pembelajaran yang mampu memfasilitasi siswa dalam mengembangkan keterampilan berpikir tingkat tinggi. Sehingga tujuan dari penelitian ini adalah untuk mendeskripsikan model pembelajaran RADEC sebagai salah satu alternatif model pembelajaran yang dinilai dapat meningkatkan pengembangan keterampilan berpikir tingkat tinggi siswa sekolah dasar pada mata pelajaran IPA. Metode penelitian ini menggunakan metode Single Subject Research yang melibatkan 4 siswa kelas V SD sebagai subjek penelitian. Salah satu solusi untuk membantu mengembangkan keterampilan berpikir tingkat tinggi pada penelitian ini adalah dengan menggunakan model pembelajaran RADEC (Read-Answer-Discuss-Explain and Create). Hal ini dibuktikan dengan proporsi overlap pada subjek yang sangat rendah, yaitu 0% yang mengindikasikan bahwa model pembelajaran RADEC berpengaruh positif terhadap kemampuan berpikir tingkat tinggi siswa. Peningkatan ini dibantu oleh sintaks pembelajaran yang dapat mengembangkan keterampilan berpikir tingkat tinggi. Kesimpulan dari penelitian ini adalah model pembelajaran RADEC mampu membantu meningkatkan keterampilan berpikir tingkat tinggi siswa.